Effectiveness and safety of zinc oxide nanoparticle-coated socks compared to uncoated socks for the prevention of pitted keratolysis: a double-blinded, randomized, controlled trial study - Punyawee Ongsri (2022)
Background: Pitted keratolysis (PK) and bromodosis have negative impacts on the quality of life especially for military personnel. The antibacterial efficacy and safety of zinc oxide nanoparticles (ZnO-NPs) make them a suitable additive for textiles. We aim to establish the ability of ZnO-NP-coated socks to prevent PK and bromodosis in a real-life setting. Materials and methods: A double-blinded, randomized, controlled trial was conducted in January 2019. Naval cadets assigned to a 14-day field training course were randomly allocated to either a ZnO-NP-coated or an uncoated-sock group. They completed questionnaires evaluating behavioral risk factors and self-assessed foot odor levels using a visual analogue scale (VAS); intervention-blinded dermatologists also performed foot examinations. They reassessed their odor levels and had their feet re-examined upon completion of the training course. Results: The 148 cadets enrolled for the study were allocated to two groups of 74 each. The ZnO-NP-coated sock participants demonstrated significantly less PK development than uncoated socks (P = 0.05). There was a reduction of the foot odor levels in both groups, as measured by the VAS, without statistical difference. However, the uncoated sock group experienced more foot odor with a significantly greater negative effect on their daily lives (P = 0.04) than the ZnO-NP-coated sock group. Conclusions: ZnO-NP-coated socks proved their efficacy in inhibiting the development of PK for military personnel.